2015
DOI: 10.1038/npjschz.2015.47
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise and yoga improve neurocognitive function in women with early psychosis

Abstract: Impairments of attention and memory are evident in early psychosis, and are associated with functional disability. In a group of stable, medicated women patients, we aimed to determine whether participating in aerobic exercise or yoga improved cognitive impairments and clinical symptoms. A total of 140 female patients were recruited, and 124 received the allocated intervention in a randomized controlled study of 12 weeks of yoga or aerobic exercise compared with a waitlist group. The primary outcomes were cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 22 publications
(18 reference statements)
4
106
3
1
Order By: Relevance
“…As shown in Tables and , 38 studies met criteria for inclusion in the qualitative synthesis and all were published after 2005 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Tables and , 38 studies met criteria for inclusion in the qualitative synthesis and all were published after 2005 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two studies reported CRF data as mean scores for VO 2 (max, peak, or predicted VO2 in ml/kg/min), and 10 of these studies included data for HC (Stage 1 = 1; Stages 1 and 2 = 1; Stage 2 = 2; Stage 3 = 5; Stage 4 = 2). Figure reports the sample sizes for each group in the 10 eligible studies, and the forest plot demonstrates the overall ES for CRF (with 95% CI) for all studies and then the ES for each clinical stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, although the findings did not show a pronounced effect on plasma BDNF, some previous RCTs demonstrated the benefits of yoga therapy in schizophrenia compared with exercise training, specifically in negative symptoms and social function [70,71,72]. A recent RCT also concluded that both aerobic exercise and yoga groups for early psychosis improved neurocognitive function [73]. Several factors may cause differences in the results of this analysis, e.g., age, completion rate, exercise intensity, and duration of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that only one RCT in the meta analysis evaluated outcomes other than clinical severity; this study evaluated face emotion recognition, but not cognitive function (Behere et al, 2011). A study in Hong Kong also compared effect of yoga and aerobic exercise on cognition among women with early psychosis; yoga enhanced attention better than aerobic exercise (Lin et al, 2015). …”
Section: Yoga As Cognitive Enhancement Therapymentioning
confidence: 99%